2023
DOI: 10.1093/europace/euad172
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis reveals influencing factors to facilitate successful anodal-ring capture in left bundle branch pacing

Abstract: Background and Aims Left bundle branch pacing (LBBP) maintains left ventricular synchrony but induces right ventricular conduction delay (RVCD). Although anodal-ring capture (ARC) during bipolar LBBP improves RVCD, it is not achieved in all patients receiving LBBP. This study aimed to analyze the factors influencing ARC implementation. Methods Patients receiving LBBP with intraoperative ARC testing were enrolled. Electrocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Our findings should be further assessed in further multicenter randomized trials with longer follow-up and larger sample size. Second, accumulated studies suggested that LBBP achieved left ventricular synchrony but induced right ventricular conduction delay[32]. Bipolar LBBP was expected to improve the bi-ventricular electrical synchrony in comparison of unipolar LBBP, futher achieving more physiological conduction system activation[33].…”
Section: Limitationsmentioning
confidence: 99%
“…Our findings should be further assessed in further multicenter randomized trials with longer follow-up and larger sample size. Second, accumulated studies suggested that LBBP achieved left ventricular synchrony but induced right ventricular conduction delay[32]. Bipolar LBBP was expected to improve the bi-ventricular electrical synchrony in comparison of unipolar LBBP, futher achieving more physiological conduction system activation[33].…”
Section: Limitationsmentioning
confidence: 99%